Crowding during restricted and free viewing - Wallace, Julian M. (2013)
Crowding impairs the perception of form in peripheral vision. It is likely to be a key limiting factor of form vision in patients without central vision. Crowding has been extensively studied in normally sighted individuals, typically with a stimulus duration of a few hundred milliseconds to avoid eye movements. These restricted testing conditions do not reflect the natural behavior of a patient with central field loss. Could unlimited stimulus duration and unrestricted eye movements change the properties of crowding in any fundamental way? We studied letter identification in the peripheral vision of normally sighted observers in three conditions: (i) a fixation condition with a brief stimulus presentation of 250 ms, (ii) another fixation condition but with an unlimited viewing time, and (iii) an unrestricted eye movement condition with an artificial central scotoma and an unlimited viewing time. In all conditions, contrast thresholds were measured as a function of target-to-flanker spacing, from which we estimated the spatial extent of crowding in terms of critical spacing. We found that presentation duration beyond 250 ms had little effect on critical spacing with stable gaze. With unrestricted eye movements and a simulated central scotoma, we found a large variability in critical spacing across observers, but more importantly, the variability in critical spacing was well correlated with the variability in target eccentricity. Our results assure that the large body of findings on crowding made with briefly presented stimuli remains relevant to conditions where viewing time is unconstrained. Our results further suggest that impaired oculomotor control associated with central vision loss can confound peripheral form vision beyond the limits imposed by crowding.